Endocrine gland development and disease - Thomas, Paul (Current topics in developmental biology, 2013)
This new volume of Current Topics in Developmental Biology covers endocrine gland development and disease, and with contributions from an international board of authors. The chapters provide a comprehensive set of reviews covering such topics as sex determination & gonadogenesis, hypothalamus, paraythyroid and placenta. Covers the area of endocrine gland development and diseaseInternational board of authors Provides a comprehensive set of reviews covering such topics as sex determination & gonadogenesis and the adrenal, thyroid and pineal glands.<